2009
DOI: 10.1016/j.brainres.2009.08.066
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrotestosterone activates CREB signaling in cultured hippocampal neurons

Abstract: Although androgens induce numerous actions in brain, relatively little is known about which cell signaling pathways androgens activate in neurons. Recent work in our laboratory showed that the androgens testosterone and dihydrotestosterone (DHT) activate androgen receptor (AR)-dependent mitogen-activated protein kinase/extracellular signal-regulated kinase (MAPK/ERK) signaling. Since the transcription factor cyclic AMP response element binding protein (CREB) is a downstream effector of MAPK/ERK and androgens a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 129 publications
(187 reference statements)
0
27
0
Order By: Relevance
“…Consistent with these findings, there is a greater distribution of androgen receptor mRNA relative to estrogen receptor mRNA in the hippocampus of adult male and female rats (Simerly et al, 1990). In the hippocampus, androgens affect synaptic plasticity (Harley et al, 2000;Pouliot et al, 1996;Sakata et al, 2000;Smith et al, 2002;Ziehn et al, 2012), acetylcholine release (Mitsushima et al, 2009), NMDA receptor binding (Kus et al, 1995;Romeo et al, 2005) phosphorylation of protein kinases (Carrier and Kabbaj, 2012;Hatanaka et al, 2009;Nguyen et al, 2005;Rossbach et al, 2007), the expression of transcription factors (Li et al, 2012;Nguyen et al, 2009), neurogenesis (Benice and Raber, 2010;Okamoto et al, 2012;Spritzer and Galea, 2007), the density of synaptic spines in area CA1 (Leranth et al, 2003), and the morphology of dendrites in area CA3 (Hatanaka et al, 2009). As would be expected, many of these cellular responses are dependent upon androgen receptors (Hatanaka et al, 2009;Nguyen et al, 2005;Okamoto et al, 2012).…”
Section: Possible Neural Mechanisms Mediating Testosterone-induced Mementioning
confidence: 61%
“…Consistent with these findings, there is a greater distribution of androgen receptor mRNA relative to estrogen receptor mRNA in the hippocampus of adult male and female rats (Simerly et al, 1990). In the hippocampus, androgens affect synaptic plasticity (Harley et al, 2000;Pouliot et al, 1996;Sakata et al, 2000;Smith et al, 2002;Ziehn et al, 2012), acetylcholine release (Mitsushima et al, 2009), NMDA receptor binding (Kus et al, 1995;Romeo et al, 2005) phosphorylation of protein kinases (Carrier and Kabbaj, 2012;Hatanaka et al, 2009;Nguyen et al, 2005;Rossbach et al, 2007), the expression of transcription factors (Li et al, 2012;Nguyen et al, 2009), neurogenesis (Benice and Raber, 2010;Okamoto et al, 2012;Spritzer and Galea, 2007), the density of synaptic spines in area CA1 (Leranth et al, 2003), and the morphology of dendrites in area CA3 (Hatanaka et al, 2009). As would be expected, many of these cellular responses are dependent upon androgen receptors (Hatanaka et al, 2009;Nguyen et al, 2005;Okamoto et al, 2012).…”
Section: Possible Neural Mechanisms Mediating Testosterone-induced Mementioning
confidence: 61%
“…In vitro studies have shown that androgens can activate both the Mitogen-activated protein kinase (MAPK) and phosphoinositide 3-kinase/Akt (PI-3k/Akt) pathways, both of which regulate cell survival (Nguyen et al, 2005; Gatson et al, 2006). Downstream of these pathways, DHT has also been shown to activate cyclic AMP response element binding protein (CREB), which is known to regulate a wide range of neurotrophic effects (Nguyen et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Since Fos is rapidly transcribed in response to neuronal firing, it is possible that neural activity influences estradiol regulation of gene expression. Hormone receptors may also regulate transcription independent of direct DNA binding by controlling the phosphorylation of cAMP‐binding protein (CREB)—a factor that regulates Fos and other genes in response to neural activity (Boulware et al, ; Fix, Jordan, Cano, & Walker, ; Nguyen, Yao, & Pike, ; Shaywitz & Greenberg, ). In primary hippocampal culture and striatal neurons, ERα localized to the postsynaptic membrane signals through group 1 or 2 metabotropic glutamate receptors (mGluRs) to promote or inhibit CREB phosphorylation, respectively (Figure b) (Boulware et al, ; Grove‐Strawser, Boulware, & Mermelstein, ).…”
Section: Gene Regulation By Steroid Hormone Receptorsmentioning
confidence: 99%